(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
Northeast part of Estonia has been subject to oil shale mining since 1916. Oil shale as main source for power industry in Estonia is mined in amount of 12 million tonnes per year. The underground production rate is about 6 million tonnes of the mineral annually. Currently three open casts and six underground mines are operating, hi past 6 underground oil shale mines have been closed. Totally 979 million tonnes of rock, including oil shale has been mined underground. Today, about 305 km2 area has 512 million m3 abandoned mine workings in the depth of 10 to 70 m below the surface. The problem is influence of underground mining and mine workings on ground subsistence and ground- and surface water regime.Mapping of potential areas of ground subsidence started in the Mining Institute of Tallinn Technical University with Maplnfo Professional. GIS is used because of need for locating the tunnels in current geographic situation. As database for digitizing and scanning, available mine maps and drawings are used. Fieldwork is included for recognizing collapse areas in nature. For further analyses, Maphlnfo features and additionally, Vertical Mapper are used.In future groundwater problems will be included in the study. The study is partially supported by Tallinn Technical University by purchasing software Maplhifo. Estonian Mapping Centre has supported the study with making available to use base map of Estonia for reference.